The Role of Social and Emotional Learning in Student Success - De Razeek Zilva (Journal of Education Review Provision, 2023)
The term "social and emotional learning" (SEL) is used to describe the method through which individuals develop the ability to identify and manage not just their own but also the emotions and behaviors of those around them. What we call "social and emotional learning" encompasses the development of competencies like "self-awareness," "self-regulation," "social awareness," and "responsible decision-making" (SEL). These skills will serve you well in both your professional and personal endeavors. The beneficial outcomes that have been related to social and emotional learning include higher test scores, improved attendance, more developed social skills, and fewer disruptive behaviors (SEL). There has been a recent trend in education toward fostering the development of students' social and emotional skills by including SEL (social and emotional learning) in classroom curricula and providing supportive learning environments.